Relasi Sosial dalam Al-Qur'an dan Relevansinya Terhadap Wacana Tafsir di Era Kontemporer - Mula Saputra, Deden; Sari, Emilia; Ahmadi, Nurul (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This research examines the discourse of Quranic interpretation regarding social relations influenced by socio-historical dynamics, epistemological biases, as well as patriarchy, sectarianism, and elitism. The objectives of this article are: (1) to trace the evolution of the construction of social relations discourse in the tradition of Islamic exegesis; (2) to identify the factors that influence it; and (3) to formulate alternative readings that are contextual and relevant. The method used is a qualitative approach with a critical-constructivist paradigm, integrating discourse criticism and social hermeneutics, with primary sources ranging from classical to contemporary tafsir texts and academic literature. The results of the study show a transformation of the interpretation paradigm from textual-linguistic to a more ethical and inclusive contextual-transformative approach. This study concludes that the discourse analysis approach enriches the methodology of interpretation, encourages the reformulation of social jurisprudence and transformative interpretation education, and revitalizes Qur'anic values in building just social relations in the contemporary era.